Adoption Status of Improved Animal Husbandry Practices and its Relationship with the Profile of Dairy Farmers in Kheda District of Gujarat - Divekar, Bharat S; Trivedi, Manoj M (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
This study was conducted to ascertain the extent of adoption of improved dairy husbandry practices and its relationship with the profile  of the dairy farmers in the Kheda district of Gujarat. The study was undertaken in four randomly selected talukas of the district, from which  100 dairy farmers were selected randomly. The study revealed that the overall extent of adoption of improved animal husbandry practices  in the study area was found to be about 62.78%. The overall highest adoption rate was for reproductive and healthcare management  (81.40 and 81.33%) followed by feeding and calf management (77.00 and 62.00%), while the adoption of scientific milking and general  management (37.60 and 37.30%) was the lowest. Education, landholding, annual income, and herd size of the dairy farmers had a  highly significant (p
Keywords: Adoption; Dairy farmers; Improved animal husbandry practices; Profile of the dairy farmers; Middle Gujarat